A systematic review of the epidemiology, pathophysiology and current management of hyperlipidaemic pancreatitis. Issue 6 (December 2018) - Adiamah, Alfred; Psaltis, Emmanouil; Crook, Martin; Lobo, Dileep N.
Summary: Background & aims: The aims of this systematic review were to define the epidemiology and pathophysiology of hyperlipidaemic pancreatitis, establish its association with clinical outcome and define management strategies. Methods: The Cochrane, Embase and Medline databases were searched, limited to the last decade, for articles on hyperlipidaemic pancreatitis. All randomised controlled trials, observational studies and case series (with a minimum of 10 patients) on hyperlipidaemic pancreatitis were included. Results: Thirty-eight studies with 1979 patients were included. The median admission triglyceride concentration was 42.8 mmol/L (range 13.6–108.6 mmol/L) [3785 mg/dL (range 1205–9612 mg/dL)]. Severe hypertriglyceridaemia (>1000 mg/dL, 11.0 mmol/L) was present in 1.7% of the adult population, and about 15–20% of these developed hyperlipidaemic acute pancreatitis. Medical management of severe hyperlipidaemia at onset of acute pancreatitis has not been investigated fully. However, tight regulation of triglyceride concentration after presentation with acute pancreatitis was found to reduce the risk of recurrence. Plasmapheresis reduced concentrations of triglycerides by up to 85%, but this did not impact morbidity or mortality. All studies included defined hyperlipidaemia as a more severe form of pancreatitis. Conclusion: The available evidence suggests an increasing risk of acute pancreatitis in patients with hyperlipidaemia and a more severe form of pancreatitis. There is some evidence to suggest biochemical benefit of using novel techniques like plasmapheresis without the desired physiological benefit. However, there is a need for an international consensus on the management of hyperlipidaemic pancreatitis. More rigorous and methodologically robust studies are required to inform such consensus guidelines.